An effective Hamiltonian approach for Donor-Bridge-Acceptor electronic transitions: Exploring the role of bath memory - Bittner, E.R. (Condensed Matter Physics, 2016)
We present here a formally exact model for electronic transitions between an initial (donor) and final (acceptor) states linked by an intermediate (bridge) state. Our model incorporates a common set of vibrational modes that are coupled to the donor, bridge, and acceptor states and serves as a dissipative bath that destroys quantum coherence between the donor and acceptor. Taking the memory time of the bath as a free parameter, we calculate transition rates for a heuristic 3-state/2 mode Hamiltonian system parameterized to represent the energetics and couplings in a typical organic photovoltaic system. Our results indicate that if the memory time of the bath is of the order of 10-100 fs, a two-state kinetic (i.e., incoherent hopping) model will grossly underestimate overall transition rate. Представлено формально точну модель електронних переходiв мiж початковим (донор) та кiнцевим
(акцептор) станами, якi зв’язанi промiжним (мiсток) станом. Наша модель включає спiльний набiр коливних мод, якi взаємодiють з донорним, мiстковим та акцепторним станами, та служить як дисипативний
термостат, що порушує квантову когерентнiсть мiж донором i акцептором. Беручи час пам’ятi термостата як вiльний параметр, ми розраховуємо iнтенсивнiсть переходiв для евристичного 3-стани/2 модового
гамiльтонiана системи, параметризованого для опису енергетики та взаємодiй в типово органiчнiй фотовольтаїчнiй системi. Нашi результати вказують, що якщо час пам’ятi термостату є порядку 10–100 пс,
дво-станова кiнетична (тобто з некогерентним перескоком) модель значно недооцiюнює загальну iнтенсивнiсть переходiв.